Tradisi, Bentuk, Nilai dan Identitas Desain Produk Abad 19-20 - Imam Santoso (PANGGUNG, 2014)
ABSTRACT The design has meaning and value. It is not only point out to the object but also refers to the dif- ference meaning contained. The design has a variety of meanings therefore no singular definition will suﬃce to explain the whole process in design. Design can refer to the knowledge, work and discourse. The process of creating a design in that sense requires consideration of aspects of unity between form, function, meaning and value. Along with the development of science, technology, art and culture, they expanded the meaning of design started by the issues of form into value that ultimately relates to identity. Through literature study of design works from some types of products in a particular period, that every country that has its roots in traditional design were not uniform in defining or classifying designs. A variety of meanings of the design can be determined design position in tradition activities, and actualize it in a diﬀerent national identity. Keywords: Education of Art, Design, Tradition, Value and Identity    ABSTRAK Desain memiliki makna dan nilai, tidak hanya mengacu pada objek tetapi perbedaan mak- na yang dikandungnya. Desain memiliki beragam arti, karenanya definisi tunggal tidak akan cukup menjelaskan seluruh proses dalam desain. Desain dapat mengacu kepada ilmu, karya maupun wacana. Proses membuat desain dalam pengertian tersebut, membutuhkan pertim- bangan aspek kesatuan antara bentuk, fungsi, makna dan nilai. Seiring perkembangan ilmu pengetahuan, teknologi, seni dan budaya, desain mengalami perluasan makna dari persoalan bentuk menjadi persoalan nilai yang pada akhirnya berkaitan dengan identitas. Melalui studi literatur karya-karya desain dari beberapa jenis produk pada masa tertentu, bahwa setiap Ne- gara yang memiliki akar dalam tradisi desain, tidak seragam dalam menentukan atau mem- buat klasifikasi desain. Dari keragaman pemaknaan terhadap desain, dapat ditentukan posisi desain dalam aktivitas tradisi, serta mewujudkannya dalam identitas nasional yang berbeda. Kata kunci: Pendidikan seni, Desain, Tradisi, Nilai dan Identitas